ANALISIS KELENGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP GUNA KELANCARAN KLAIM JKN DI RUMAH SAKIT BETHA MEDIKA - Irna Melawati, (Journal of Innovation Research and Knowledge, 2021)
This study aims to analyze the completeness of filling in inpatient medical resumes in order to smooth JKN claims at Betha Medika hospital. This research method uses descriptive research methods with a qualitative approach. The method of collecting data by means of observation, documents, interviews and literature study. The sampling technique used purposive sampling with a sample of 85 files. The results of this study found that the completeness of filling out a medical resume and all contents were complete. Meanwhile, the names of the guardians, gender, DPJP signature, history taking, physical examination, supporting examinations, diagnos, actions, therapy, and conditions at the time of discharge were still incomplete. The problems found include some claims experiencing delays, not eligible for claims on some JKN claims, delays in claims caused by BPJS regulations during the COVID-19 pandemic and frequent internet network disruptions so that the claim process is disrupted. The results of this study suggest implementing effective communication to the DPJP, the director's policy regarding filling out medical resumes, re-evaluating several files by verifiers regarding incomplete patient discharge summaries, optimizing existing Human Resources (HR), and grading the server used so that no internet error occurs.